Principle of consent for organ donation in Malaysia / Khairul Anuar Abdul Hadi, Nur Khalidah Dahlan and Allycia Taidin - Abdul Hadi, Khairul Anuar; Dahlan, Nur Khalidah; Taidin, Allycia (2006)
Our Human Tissue Act 1974 is considered outdated and had not clearly stated whose lawfully possess the body of deceased should objection arises due to the consent given before. The term 'tissue' or 'death' or 'lawful in possession of a body' and 'the hierarchy of relatives deemed to be next of kin' also did not classify in the act. This research will analyze the significance of consent. It looks into the view both medical ethic and morality. Our research is based on the qualitative methodology whereby apart from references to the books, article and journals we also conducted interview with several lectures and official expertise in this field. This research is aim to answer the question on validity of consent given by the donor when there is an objection against the wishes of the deceased and to see whether our act is sufficient to cover organ donation. The Human Tissue Act 1974 is the only main legislation in Malaysia. It is also consider being ambiguous. This research intends to make the Act become more specific and clear. As the Act mentioned only about cadaver donors, we hope that the terms of living donor also included in the Act.